PRODUCTION OPTIMIZATION STRATEGY OF CERAMIC SCREENED WELL - Khamim Mustofa, Fajar
One of the major issues dealing with high deliverability gas wells is the sand production from unconsolidated formation. Related to this issue, in order to develop shallow gas reservoirs in the Mahakam Delta, it needs a cost-effective completion solution to produce gas from multi-layered and the unconsolidated sands. Multi-Zone Single Trip Gravel Packs (MZ-STGP) have been installed in the majority of gas wells, but they have technical restrictions in terms of zone spacing, the number of zones, well deviations and pumping gravel cost prompted the need to develop advanced completion technique. Lean Six Sigma methodology helps to identify the defects of previous sand control prevention and to choose the best feasible solution. Through Lean Six Sigma deep investigation, the cased hole ceramic sand screen has been chosen as the best method in facing the sand problems. For simpler and quicker installation on the Tunu gas wells, the free hanging mode is selected. The ceramic sand screen is hung at the SSD and the SSD also has been used for gas production route. Two zones are completed using a ceramic screen, with the specification of 12 gauge slot opening (300 microns) and 10 ft screen length. By utilizing the ceramic screen, it simplifies the completion design due to removing gravel pack stimulation as an attempt to reduce the total well cost. In technical terms, no sand is observed on the surface during the production phase from both zones. From an analysis, skin value are about 13 and 71 as a result of applying the ceramic screens for zone 1 and 2, respectively. A real gas pseudo-pressure approachment is used to calculate the skin factor. By adjusting the bottom hole pressure, the skin factor is reduced while maintaining high gas production rate. The production optimization strategy is conducted by using the rule of thumb 40-70% of AOFP and validated using the gas well production optimization by Dawud et al method. For zone 1, the optimum production is in a range of 1.3 – 2.55 MMSCFD by adjusting Pwf 800 – 1,150 psia with resulting skin value of 10 – 13. For zone 2, the optimum production can be achieved in a range of 0.96 – 1.68 MMSCFD by adjusting Pwf 1,150 – 1,600 psia with resulting skin value of 52 – 67.